Responsibilities and Roles of Nurses About Patient Health Confidentiality at Home Sick - Saputra, M. Khalid Fredy; Cahya, Mochamad Robby Fajar; Rukayah, Siti; Dunggio, Abdul Rivai Saleh; Nasution, Titi Anggraeni; Fitriyanstanti, Devi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Every National Development Efforts must based with outlook health in meaning development national must notice health society and is not quite enough answer party Good government or public. Violation law in implementation service health if happen can requested accountability law or in other words done enforcement law. All identified information regarding health status patient, condition medical, diagnosis, prognosis, and action medical and all other information of that nature personal, must guarded confidentiality by someone nurses, even after death. Research result show that form Legal Responsibilities of Nurses Must Save Patient Health Secrets, consisting of on not quite enough answer related administration with permission as nurse, bear it answer related civil law with default nor deed oppose law, as well not quite enough answer related crimes with violation fulfilling prohibitions element follow criminal. Factors that become obstacles and solutions not quite enough answer law nurse to confidential health patient, starting from action breach of contract committed by the nurse. That matter happen Because nurse negligent or not on purpose leak confidential health patient as well as nurse consider condition health patient is matter normal and not confidential. Consequence law for negligent nurse to must save confidential health patient will law oriented administrative, civil and criminal.